2018
DOI: 10.1111/tops.12355
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Language and Cognition: Evidentiality and Sources of Knowledge

Abstract: Understanding and acquiring language involve mapping language onto conceptual representations. Nevertheless, several issues remain unresolved with respect to (a) how such mappings are performed, and (b) whether conceptual representations are susceptible to cross-linguistic influences. In this article, we discuss these issues focusing on the domain of evidentiality and sources of knowledge. Empirical evidence in this domain yields growing support for the proposal that linguistic categories of evidentiality are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 105 publications
0
12
0
1
Order By: Relevance
“…In the last paper of this set, Ünal and Papafragou () examine what one might call learning " really hard" meanings, that is, evidentials, which mark the source of information provided by a given verb. The authors offer this case as an opportunity to explore the complexities of the relationship between learning the meanings of these markings, and the underlying conceptual knowledge which must (by some accounts) be available for the child to learn these meanings.…”
Section: Learning (Really) Hard Words: Challenges and Opportunities Fmentioning
confidence: 99%
“…In the last paper of this set, Ünal and Papafragou () examine what one might call learning " really hard" meanings, that is, evidentials, which mark the source of information provided by a given verb. The authors offer this case as an opportunity to explore the complexities of the relationship between learning the meanings of these markings, and the underlying conceptual knowledge which must (by some accounts) be available for the child to learn these meanings.…”
Section: Learning (Really) Hard Words: Challenges and Opportunities Fmentioning
confidence: 99%
“…The demonstration that bodily metaphors operate at both language and conceptual levels highlights the complexity of the interface between linguistics and cognition. The relationship between language and cognition remains disputed, but recent scholarship suggests that they are more entwined than classical models would have us believe (Ünal and Papafragou ). The details of how language and cognition are related are beyond the scope of the present article; however, the examination of embodied cognition and its implications for future scenarios in which human embodiment undergoes drastic alteration understands language to be a component of cognition, rather than an entirely separate domain.…”
Section: Metaphor and Embodimentmentioning
confidence: 99%
“…Research has consistently shown that until around the age of six or seven, children's command of these strategies is not fully adult-like (e.g. in Tibetan;de Villiers et al 2009), and children's comprehension lags behind their production (Papafragou et al 2007, Ünal & Papafragou 2016, Ünal & Papafragou 2018, Winans et al 2015. This asymmetry is notable not only for its robustness across languages and evidential typologies, but also because it is the reverse of many other productioncomprehension asymmetries in language -children often understand linguistic forms before they produce them (Goldin-Meadow, Seligman & Gelman 1976, Gertner, Fisher & Eisengart 2006.…”
mentioning
confidence: 99%